Determining the parameters and chemical behaviour of the overdriven detonation reaction zone of CL-20-based aluminized explosives - Moyan Liu; Yan Liu; Fan Bai; Hongfu Wang; Shanyong Chu; Fenglei Huang (Defence Technology)
The new CL-20 (hexanitrohexaazaisowurtzitane) type aluminized explosives in the overdrive detonation (ODD) conditions of the core problem is how to accurately represent the state of the overdrive detonation products. To this end, this paper is based on the impedance matching method to test the ODD conditions of CL-20 type aluminium explosive particle velocity. Calculated the interfacial pressure of the shock wave in different media. Determined the characteristic parameters of the reaction zone of the detonation of CL-20 aluminized explosives. Calibrated the parameters of the Jones–Wilkins–Lee (JWL) + γ equation for the detonation products (DPs). Revealed the effect of different DPs equation of state (EOS) on the Hugoniot pressure of ODD. The results indicate that when the content of aluminum powder ranges from 0% to 30%, the duration of the ODD reaction zone and the width of the detonation reaction zone of the CL-20-based aluminized explosive are directly proportional to the content of aluminum powder. The width of the detonation reaction zone is increased by 1.97 times to 2.7 times compared to that of the reaction zone without the addition of aluminum powder. However, the energy release efficiency of the detonation reaction zone is inversely proportional to the content of aluminum powder. When the aluminum powder content was held constant, the incorporation of AP caused a 25% reduction in the energy release efficiency of the detonation reaction zone. Compared with existing ODD state equations, the JWL + γ equation is superior in calibrating overpressure Hugoniot data and the isentropic expansion in the C-J state. The deviation between calculated pressure results and experimental measurements is within 6%.